Penerapan Model Pembelajaran Inkuiri Terbimbing (Guided Inquiry) untuk Meningkatkan Hasil Belajar Kimia pada Siswa SMK - Mujiyati Mujiyati (Paedagogie, 2020)
This article present an application of guided inquiry learning model and optimization of structured task to improve chemistry learning outcomes and form good character in class XEA students of SMK Negeri I Magelang for the 2018/2019 academic year. This Reseach was conducted in 2 cycles, each cycle data collection and analysis were carried out. The assesment is carried out based on student answer and results of the evaluation of each competency studied. The result showed a significant relationship between learning with the guided inquiry learning model and the optimization of structured task with chemistry learning outcomes and good character building in student.